The Ummatic Elements in Malaysia-Turkey Economic Cooperation: A Study on Investment Aspects - Mohamad Shaukhi Mohd Radzi; Mohd Sohaimi Esa; Zaini Othman (BASKARA : Journal of Business and Entrepreneurship, 2023)
The investment aspect is one of the most important aspects in strengthening the economy of a country. As countries that practice an open economic policy, Malaysia and Turkey emphasize the investment aspect of whether Foreign direct investment (FDI) and Direct Investment Abroad (DIA). Malaysia and Turkey are also major players in the Organization of Islamic Cooperation (OIC) and the Economic Cooperation Organization of Eight Developing Countries (D-8). It turns out that these two Islamic organizations have succeeded in becoming catalysts in improving the economy of both countries. These two organizations also clearly make the ummatic agenda the main agenda of the establishment as well as fighting for the welfare of Muslims. This is proven that the amount of investment for these two countries is increasing over time. The diversity of investment sectors is also seen to be increasing based on the needs of Malaysia and Turkey. This study uses a qualitative method that leads to the study of the discipline of history by emphasizing the analysis of primary sources, secondary sources and interviews to produce an authoritative study.